Educação e paisagem : tecendo elos para a educação ambiental - Pedrotti, Débora Eriléia (2005)
Cuiabá is a city present to us nowadays as a big city, where the environmental problems grow in a huge and disordered scale. Its original landscape was totally modified by human beings and actually shows the inherent problems to the brazilian metropolis. But we expose its initial landscape through its remnant green areas, where commonly we find traces of original species of regional flora and fauna that constituted the local vegetation, where the city is builded today.Using this landscape this search tryed to check the environmental perception of students from 1st.Grade of High School Escola Estadual “José de Mesquita”, about remnant green area called “Mata Semi-Decídua” (Campo de Bode), located at Porto neighborhood, in Cuiabá-MT, making links to the Environmental Education, considering that in the contemporary urban life the physical contact with the natural environment is more and more indirect and limited to special occasions. The methodological option drived to the qualitative method, using the data colect instruments, that were questionnaires and interviews, and like pedagogical didatic strategies we realized one field class at the green area and after, the students produced texts inside the class.Beyond the flora and fauna reserves the green area actually is being used as relax places, leisure and refuge to cuiabanas families, as well to minimize the “heat island” expansion, to ensure the urban conservation area and to protect fountains that contribute to Cuiabá River.Some of these areas were studied before and were structured as green areas through the municipal decret and are visited for a great part of population, as for example Parque Mãe Bonifácia, Morro da Luz e Horto Florestal Toti Garcia, where frequently social and cultural events occur, and also the scientific search development. In this direction rises the insertion of Environmental Education pratice, in these exuberant landscape spaces, where the school insert itself as precursory of the act to make sensible these people to environmental values changes, and this way has its role based on making the people responsible to the environmental maintenance.